Governments-in-exile on jewish rights - Gottschalk, Max; American Jewish Committee (New York : American Jewish Committee, 1942)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: regeringen in ballingschap; joods vraagstuk